The duality persists - Hurst, Matthias (Universitätsbibliothek Johann Christian Senckenberg)
The following examples prove the richness of the Faust tradition in cinema, its importance as part of modern culture and the effectiveness of the two sketched dualities related to Faust on the screen.
urn:nbn:de:hebis:30:3-434468